(untitled) (Journal of history, 2019)
The article sheds some light on the strategies employed by Kazakh men to construct a new attitude to woman through analysis of B.Mailin «Raushan communist». The writer gives a vague contours of how Kazakh men and new perception of masculinity could be formed – responsible, consciously acting for the cause of the new Order. In the Kazakh culture and core of Kazakh ethnicity the masculine/male beginning dominate. How to save it? B.Mailin in his works develops concepts and recipes of new Kazakhness/Kazakh code through и revision of male dominance recharged by the new/Soviet power. Mailin perceives women emancipation from way of life not along the traditional society destruction and men’s deprivation of their masculinity (property, priority in decision making, the right to control wives behavior, sedentarization), but in line with trajectory of men changed attitude to new canals of social mobility for women opened by the soviet regime.